Talking to strangers : what we should know about the people we don't know - Gladwell, Malcolm, 1963- (Back Bay Books, Little, Brown and Company, 2021)
The popular podcast host and author explores how people interact with strangers and why these exchanges often go wrong, offering strategic tips for more accurate and productive interactions.